2022
DOI: 10.1002/ima.22765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise and noninvasive brain stimulation on cognition and dementia of elderly people with frailty: A randomized study

Abstract: The objective was to verify the effects of intervention with physical and mental exercises (PMED) and noninvasive brain stimulation (NIBS) on cognition and dementia of frail elderly people with mild cognitive deficits. Sixty elderly people (aged 65–80 years) were divided into three groups, an experimental group (GAE) that received intervention with PMED plus NIBS, a control group for physical exercises (GCA), which received only the PMED, and the third also control non‐invasive brain stimulation group (GCF) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…In this trial, the intervention proved beneficial for the primary outcome (dementia symptoms and cognition) and the secondary outcome (Brain wave) in those individuals who received the full intervention. This finding is consistent with our previous study in different groups, as frail elderly [47].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this trial, the intervention proved beneficial for the primary outcome (dementia symptoms and cognition) and the secondary outcome (Brain wave) in those individuals who received the full intervention. This finding is consistent with our previous study in different groups, as frail elderly [47].…”
Section: Discussionsupporting
confidence: 94%
“…Previously, we demonstrated that the combination of NIBS with PMED was able to improve the cognition concomitantly the modulation of the brain waves of older people with mental and physical frailty [47]. Here only the combined intervention (PMED plus NIBS) improved working memory, which is the most evident impairment of Alzheimer's disease [47].…”
Section: Discussionmentioning
confidence: 88%
“…General exercises: Six of the selected papers conducted Randomized Controlled Trials [26,119,121,123,124,150], one nonrandomized clinical study [117], one pilot study [122], one quasi-experimental intervention study [126], and one cohort study [125]. The majority of the studies included participants with ages above six years.…”
Section: Study Characteristicsmentioning
confidence: 99%